Biodiversity and medicinal uses of globe artichoke (Cynara scolymus L.) plant - Bekheet, S; Sota, V (Journal of Biodiversity Conservation and Bioresource Management, 2019)
Globe artichoke (Cynara scolymus L.) is a vegetable crop native of the Mediterranean basin and it is grown mainly for its immature flower buds. The edible parts of artichoke have important nutrition values to their content of inulin, fibers and minerals. Furthermore, artichoke is recognized as a medicinal plant where leaves and heads are rich source of polyphenolic compounds. It is recommended for the treatment of gallstones, liver disease or damage and poor liver function. The pharmaceutical properties of artichoke are linked to their special chemical composition, which includes high levels of polyphenols such as cynarin, along with its biosynthetic precursor chlorogenic acid. Globe artichoke is characterized by a wide range of biodiversity which represents a prerequisite for genetic improvement. However, there are many factors including biotic and abiotic stresses threatening the genetic resources of globe artichoke. Such factors could result in genetic erosion due to crop failure and loss of cultivars. Therefore, there is a great need to preserve the globe artichoke diversity for future genetic improvement. Because most cultivars are highly heterozygous, maintenance of globe artichoke germplasm in seed form is restricted. Otherwise, conservation in the field presents major drawbacks, which limit its efficacy and threaten the safety of germplasm conserved in this way. The application of biotechnology tools, i.e. plant tissue culture and molecular biology technique can provide reliable methods for supporting the exploitation and conservation of globe artichoke biodiversity. Furthermore, in vitro culture techniques could be used for the controlled production of artichoke secondary metabolites. This article discusses the biodiversity, conservation and nutritional and medicinal aspects of globe artichoke plant. J. Biodivers. Conserv. Bioresour. Manag. 2019, 5(1): 39-54